Integrating Social Service into Student Camp & Tour Activities: A Community Engagement Program at Gunung Laya, Majalengka - Vina Andita; Abrar Farhan Sudibyo (PT. Berkah Digital Teknologi, 2026)
The Camp & Tour activity is not only a recreational program for students, but can also be developed as a medium for community service through social care-based activities. This article aims to describe the implementation of student social concern in the Camp & Tour program of Institut Budi Utomo Nasional (IBUN) Majalengka through a social service activity. The program was conducted at Gunung Laya (GL-20), Argasari Village, Talaga District, Majalengka Regency, with 45 underprivileged households and elderly residents as the main beneficiaries. The activity was implemented using a participatory community service approach through several stages, namely preparation, location survey, coordination with local community leaders, fundraising and logistics preparation, distribution of basic-needs packages, environmental clean-up activities, light educational sessions, observation, and student reflection. The evaluation was conducted descriptively through field observation, documentation of activities, informal community responses, and student reflection after the program. The results show that the integration of social service into the Camp & Tour program can transform outdoor student activities from purely recreational events into meaningful community engagement. The program provided direct material benefits through the distribution of basic-needs packages, encouraged environmental awareness through collective clean-up activities, and strengthened students’ empathy, teamwork, leadership, and sense of social responsibility. In addition, the positive response and participation of local residents indicate that the program helped build institutional relations between the campus and the local community. This activity demonstrates that Camp & Tour can be directed as a practical model of student-based community service that integrates recreation, character building, and social contribution.